2016
DOI: 10.2109/jcersj2.16009
|View full text |Cite
|
Sign up to set email alerts
|

In situ time-resolved dispersive X-ray absorption fine structure analysis of BaTiO<sub>3</sub>&ndash;LiCoO<sub>2</sub> composites for lithium ion batteries

Abstract: In this study, in situ time-resolved dispersive X-ray absorption fine structure (DXAFS) analysis of BaTiO 3 LiCoO 2 (BTLC) composites for lithium ion batteries was performed to characterize the cobalt ion valence shift between oxidized and reduced states of driven cells, in an attempt to better understand the contribution of ferroelectric solid electrolyte interfaces (SEIs) to chargedischarge rates. Two types of artificial SEIs, ferroelectric BT and paraelectric Al 2 O 3 , were compared. The magnitude of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…The sharp rise in temperature to the target crystallization temperature of 600 °C, without holding at intermediate temperatures at which LC decomposes in heated octylic acid as mentioned above, yielded a single-phase BT. In our previous study, 22) the XAFS spectra near the Co K edge revealed that the BT-LC composite soaked into the acetic acid followed by sintering at 600 °C for 20 h, corresponding to the same sintering condition of the MOD-3, exhibited slightly broader X-ray absorption peaks than the bare LC. This result indicates that the soaking of the LC into the acid slightly reduces the Co ion from Co 3+ to Co 2+ .…”
Section: Synthesis Of Bt-lc Composite Via Mod Routementioning
confidence: 80%
See 2 more Smart Citations
“…The sharp rise in temperature to the target crystallization temperature of 600 °C, without holding at intermediate temperatures at which LC decomposes in heated octylic acid as mentioned above, yielded a single-phase BT. In our previous study, 22) the XAFS spectra near the Co K edge revealed that the BT-LC composite soaked into the acetic acid followed by sintering at 600 °C for 20 h, corresponding to the same sintering condition of the MOD-3, exhibited slightly broader X-ray absorption peaks than the bare LC. This result indicates that the soaking of the LC into the acid slightly reduces the Co ion from Co 3+ to Co 2+ .…”
Section: Synthesis Of Bt-lc Composite Via Mod Routementioning
confidence: 80%
“…We have reported the influence of ferroelectric artificial SEIs on the high rate capabilities of LIBs, [19][20][21][22] including decoration of LC with barium titanate (BaTiO 3 ; BT), via a simple liquid phase reaction using Ba acetate and Ti alkoxide as metal precursors. The effect of the BT loading amount on the resulting high rate capability was investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Al 2 O 3 -LC was annealed at 800 °C for 20 h, which are the optimized sintering conditions described elsewhere. 12) Individual cell construction was accomplished by taking the respective synthesized composite powder, acetylene black, and poly(vinylidene fluoride) (PVDF) with a weight ratio of 7 : 2 : 1. These were then mixed into the solvent and integrated into a 2032-type coin cell for evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…In alignment with this idea, we have been reporting on the markedly enhanced power densities of the LIB cathodes modified with ferroelectric solid electrolyte interfaces (SEIs). [8][9][10][11][12] Amongst these SEIs, the ferroelectric BaTiO 3 (BT) decoration of LiCoO 2 (LC) matrices has shown much promise, exhibiting excellent rate performance. Sol-gelsynthesized 1 mol % BT-LC structures displayed a capacity of 146 mAh=g at a high rate (i.e., 10C).…”
Section: Introductionmentioning
confidence: 99%